EFEKTIVITAS DAN KONTRIBUSI PAJAK PARKIR TERHADAP PENDAPATAN ASLI DAERAH KOTA BANJARMASIN TAHUN 2018-2020 - Olifia Mita Injelina; Sustinah Limarjani; Kadir (JRUP: JURNAL REFERENSI DAN ULASAN PERPAJAKAN, 2021)
Banjarmasin is a city that on average has a motorized vehicle. Therefore, researchers took objects in Banjarmasin to find out how effective the Parking Tax is on the PAD of the city of Banjarmasin. The results of this study indicate that the parking tax collection in Banjarmasin is categorized as very effective, it can be seen from the realization of parking tax receipts from 2018-2020 reaching an average of 104.64% and all contributions obtained from the Parking Tax to the PAD of Banjarmasin City in 2018 -2020 an average of 3.16%.